Histomorphometric evaluation of implants coated with enamel or dentine derived fluoride-substituted apatite - OKTAR, FAİK NÜZHET (SPRINGER, 2008)
Objectives The aim of this study was to compare osseous healing characteristics of titanium implants coated with enamel-derived fluoride-substituted apatite (EFSA) or dentin-derived fluoride-substituted apatite (DFSA). Methods Fluoride-substituted apatite was derived from extracted human teeth with calcination method at 850 degrees C. DFSA and EFSA were separated and carefully ground with a blade grinder. Twenty-four titanium implants were prepared from a 99.99% pure titanium bar. EFSA and DFSA powders were sprayed separately on implants. As control group, unsprayed and sandblasted pure titanium implants were used. Eight adult rams were used in the study. One EFSA coated, 1 DFSA coated and 1 control implants were placed into right tibia of each rams. The rams were sacrificed after 6 months of healing. Undecalcified sections were prepared according to Donath's method and histomorphometric evaluation of implants was made. Results The mean bone contact percentage of DFSA-coated, EFSA-coated and control implants was 89.88% +/- 2.34, 70.19% +/- 13.11 and 53.12% +/- 5.76 respectively. This study suggests that DFSA-coated implants achieved better bone contact than EFSA-coated implants (P < 0.05). Also study groups presented better bone contact than control group (P < 0.05). Conclusions The results of this study show that although DFSA-coated implants achieved better bone contact, both DFSA and EFSA can be considered as appropriate coating materials.
Keywords: PLASMA-SPRAYED COATINGS; HYDROXYAPATITE COATINGS; SURFACE CHARACTERISTICS; TITANIUM IMPLANTS; BONE; FLUORAPATITE; HYDROXYLAPATITE; MAGNESIUMWHITLOCKITE; OSSEOINTEGRATION; INTEGRATION